A difference analogue of Cartan's second main theorem for meromorphic mappings - Nguyen Van Thin (Հայաստանի ԳԱԱ)
In this paper, we prove a difference analogue of Cartan's second main theorem for a meromorphic mapping on Cm intersecting a finite set of fixed hyperplanes in general position on Pn(C): As an application, we prove a uniqueness theorem for a class of holomorphic curves by inverse images of n + 4 hyperplanes. Òhis result is so far the best result about the uniqueness problem for holomorphic curves by inverse images of hyperplanes.
Keywords: Mathematics; Science